Discriminação fonêmica, processamento auditivo e reflexo acústico em crianças com desenvolvimento de fala normal e desviante - Attoni, Tiago Mendonça (2009)
This study had aim to assessment the ability to phonemic discrimination, the auditory processing and acoustic reflex thresholds in children with phonological and analyze a possible association between these aspects. Furthermore, the results were compared to children without phonological disorders. The sample consisted of 46 children, 24 with normal speech development, and 22 with deviant speech development, aged between 5:0 and 7:4. In the assessment of phonemic discrimination test was used for Figures for Phonemic Discrimination. For the evaluation of auditory processing were assessed using the Simplified Evaluation of Auditory Processing Test, Pediatric Speech Intelligibility (PSI), Speech in Noise Test, Test spondaic (SSW) and the dichotic listening test. The acoustic reflex thresholds were measured by the audiometer the frequencies 500, 1000, 2000 and 4000 Hz for the statistical analysis was performed using the SAS user's guide: statistical, Analysis System Institute Inc., Cary, NC, 2001; Spearman's correlation coefficients of Pearson, considering p <0.05. The results indicated that children with phonological deficits as the ability to phonemic discrimination, changes in auditory processing and acoustic reflections off the normal standards. The conclusion of this study is that changes in phonemic discrimination, auditory processing and acoustic reflex are associated with phonological and possibly may be responsible for his appearance.